2016
DOI: 10.1016/j.biomaterials.2015.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally photoradiation-controlled intratumoral depot for combination of brachytherapy and photodynamic therapy for solid tumor

Abstract: In an attempt to spatiotemporally control both tumor retention and the coverage of anticancer agents, we developed a photoradiation-controlled intratumoral depot (PRCITD) driven by convention enhanced delivery (CED). This intratumoral depot consists of recombinant elastin-like polypeptide (ELP) containing periodic cysteine residues and is conjugated with a photosensitizer, chlorin-e6 (Ce6) at the N-terminus of the ELP. We hypothesized that this cysteine-containing ELP (cELP) can be readily crosslinked through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The unique physicochemical properties of nanoparticles offer the opportunity to integrate different theranostic modalities within a single nanoplatform for combination therapy together with imaging. The enhanced antitumor capacity of combination therapy has been demonstrated with non-stem cancer cells [19,2327]. However, no study was reported to investigate the combination of chemotherapy, PDT, and PTT for killing the CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The unique physicochemical properties of nanoparticles offer the opportunity to integrate different theranostic modalities within a single nanoplatform for combination therapy together with imaging. The enhanced antitumor capacity of combination therapy has been demonstrated with non-stem cancer cells [19,2327]. However, no study was reported to investigate the combination of chemotherapy, PDT, and PTT for killing the CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy of depot-forming hydrogels is based on in-situ phase separation, which can be induced by changing the solubility of the polymer with respect to induction of pH, 48 temperature, 4950 ultrasound, 51 or radiation. 52 Due to the acidic tumor microenvironment of head and neck cancers, it is desirable to incorporate pH-sensitive linkages, e.g., ester linkage, or thermo-sensitive linkages into DH formulations. It will not only release chemotherapeutic agents but disintegrate the drug-loaded dendrimer cargos in a synergistic manner.…”
Section: Discussionmentioning
confidence: 99%
“…The T t can be tuned to between room and physiological temperature by control of two sequence‐specific variables: 1) hydrophobicity of the guest (X residue). ELPs that contain guest amino acids with moderately hydrophobic side chains (e.g., valine, isoleucine, and alanine) phase separate below 37 °C across a range of ELP MWs . 2) MW: for a given ELP sequence the T t can be further tuned by its MW as the T t decreases with increasing MW.…”
Section: Injectable Elp Drug Depots and Hydrogelsmentioning
confidence: 99%
“…ELPs that contain guest amino acids with moderately hydrophobic side chains (e.g., valine, isoleucine, and alanine) phase separate below 37°C across a range of ELP MWs. [204][205][206][207][208][209][210][211][212] 2) MW: for a given ELP sequence the T t can be further tuned by its MW as the T t decreases with increasing MW. Simultaneous optimization of both variables is usually sufficient to design an ELP that will phase separate at a defined concentration in a narrow temperature range of interest.…”
Section: Injectable Elp Drug Depots and Hydrogelsmentioning
confidence: 99%